PERSPECTIVES OF BLOCKCHAIN TECHNOLOGY IN THE CONTEXT OF THE GROWTH OF SOCIETY WELFARE - Aleksei Zavarzin (Вестник Северо-Кавказского федерального университета)
The article gives a detailed analysis of perspective development of Blockchain. The technology has wide applications in many spheres. It is spoken about the features and differences between various Blockchain systems. Much attention is given to the main advantages and disadvantages of the technology. The author provides the analysis of popular cryptocurrencies. Experts' forecasts on the volume of investments in the Blockchain market up to 2021 are noted. The potential effect of technology introducing on the welfare of citizens is forecast.